Treatment of chronic venous disease with flavonoids: recommendations for treatment and further studies. (September 2013) - Rabe, E; Guex, J-J; Morrison, N; Ramelet, A-A; Schuller-Petrovic, S; Scuderi, A; Staelens, I; Pannier, F
Objectives: A variety of studies have suggested that flavonoids are effective for the treatment of CVD. However, many questions remain about their mechanism of action and when, how, and for what signs and symptoms they should be used. Method: A panel of experts in CVD met in Budapest, Hungary in December 2011 to discuss the current state of knowledge of CVD and the role of flavonoids in its treatment. The discussion was based on a literature search in the current databases. The goals of this paper are recommendations for further studies on the use of flavonoids in the treatment of CVD. Results: There is good evidence to recommend the use of flavonoids in the treatment of CVD. However, because of the poor quality of some older clinical trials, inadequate reporting, and insufficient information, much work is still needed to firmly establish their clinical efficacy and to determine when and how they should be employed. In particular, long-term randomized, placebo-controlled, double-blind studies are needed to establish the efficacy and safety of flavonoids. Additional studies are also needed to establish their mechanism of action, pharmacokinetics, toxicity, and cost-effectiveness. Conclusions: Aside from good evidence for the use of flavonoids in CVD further studies are indicated to establish long term treatment in this indication.